Os direitos territoriais e as territorialidades quilombolas: o caso da comunidade quilombola do Cedro, em Mineiros, sudoeste goiano - Damasceno, Mayron Morais (2022)
The present work seeks to explain the contemporary condition of territorial rights and its relationship with the Brazilian justice system and the ethnification processes of the Quilombola do Cedro Community, located in the city of Mineiros, southwest of Goiás. The relevance of this research is anchored in the fact that the cedars, since their origins, maintain the continuity of their ways of living on their traditionally occupied territory. As a hypothesis to be investigated, it will be verified the way in which the justice system relates to and makes effective the ethnification processes, through the guarantee of identity recognition and the process of territorial regulation. In turn, its central objective is to understand the legal relationship between the demarcation of the claimed territory and the forms of protection of its territorial rights. The specific objectives consist of critically discussing the historical-political context of the formation of Quilombola Communities in the Brazilian scenario, analyzing the influence of the main economic cycles. To understand the study of quilombola territorial issues as an emergency evidenced by the processes of ethnification that deserves to be deepened in the field of studies of Agrarian Law. To describe the territorial formation of the city of Mineiros and the Quilombola Community of Cedro, understanding its historical and social evolution, as well as its spatialities and ethnic identity. Finally, to discuss territorial issues in the face of the process of ethnification of the Cedars and their relationship with the justice system through the interpretation of Public Civil Action n. 0000581-43.2016.4.01.3507 and the Administrative Procedure for Territorial Demarcation with INCRA, proposing a multicultural vision about quilombola tenure. The construction of a critical view, through the dialogue between processes of ethnification, possession and property from the perspective of Agrarian Law and Anthropology, aims to understand and deepen the emergence of a group in the fight for the protection of its territorial rights, cultural and identity. The methodological construction of this qualitative research will be carried out based on the bibliographic review and the analysis of information extracted from books, theses/dissertations, academic works, scientific articles and electronic sites of public agencies, as well as the study of a concrete case.